Gas exchange and water relations of young potted loquat cv. Algerie under progressive drought conditions - A. Stellfeldt; M.A. Maldonado; J.J. Hueso; J. Cuevas (Journal of Integrative Agriculture, 2018)
Relationships between plant water status and gas exchange parameters at increasing levels of water stress were determined in Algerie loquats which grown in 50 I pots. Changes in soil water content and stem water potential and their effects on stomatal conductance (Gs) and net photosynthesis (Pn) rate were followed in control plants and in plants without irrigation until the latter reached near permanent wilting point and some leaf abscission took place. Then, the irrigation was restarted and the comparison repeated. Soil water content and stem water potential gradually diminished in response to drought reaching the minimum values of 0.9 mm and −5.0 MPa, respectively, 9 days after watering suspension. Compromised plant water status had drastic effects on Gs values that dropped by 97% in the last day of the drought period. Pn was diminished by 80% at the end of the drought period. The increasing levels of water stress did not cause a steady increase in leaf temperature in non-irrigated plants. Non-irrigated plants wilted and lost some leaves due to the severity of the water stress. However, all non-irrigated plants survived and reached similar Pn than control plants just a week after the irrigation was restarted, confirming drought tolerance of loquat and suggesting that photosynthesis machinery remained intact.